Determination of Glycyrrhetic Acid in Rat Plasma by HPLCAfterOral Administration of Licorice Aqueous Extract: Detection of glycerrhetic acid in rat serumwas - Shamsa, Fazel; Souri, Effat; Sharifzadeh, Mohammad; Jalalizadeh, Hassan; Farzami, Payam (Iranian Journal of Pharmaceutical Sciences, 2007)
Licorice is obtained from Glycyrrhiza glabra(G. glabra) in Iran. Glycyrrhizinis the main constituent of G. glabraand has several pharmacological effects. It ishydrolyzed to glycyrrhetic acid (GA) in the intestine after oral administration. Inthis study, a novel HPLC method was used to determine the concentration of GAin rat plasma after oral administration of licorice aqueous extract. The method waslinear (r2>0.999) in the range of 0.1-5.0 μg/ml for GA. Maximum plasmaconcentration of GAwas achieved 8 h after oral administration of licorice aqueousextract. The developed method was suitable for determination of GAin rat plasma.